Microcystis sp. AE03 strain in Dal Lake harbors cylindrospermopsin and microcystin synthetase gene cluster - Bashir, Fahim; Bashir, Arif; Rajput, Vishnu D.; Bouaïcha, Noureddine; Fazili, Khalid M.; Adhikari, Samrat; Negi, Yogesh; Minkina, Tatiana; Almalki, Waleed Hassan; Ganai, Bashir Ahmad (Frontiers in Sustainable Food Systems, 2022)
Cyanobacterial harmful algal blooms (CHABs) are increasing at an alarming rate in different water bodies worldwide. In India, CHAB events in water bodies such as Dal Lake have been sporadically reported with no study done to characterize the cyanobacterial species and their associated toxins. We hypothesized that this Lake is contaminated with toxic cyanobacterial species with the possibility of the presence of cyanotoxin biosynthetic genes. We, therefore, used some of the molecular tools such as 16S ribosomal DNA, PCR, and phylogenetic analysis to explore cyanobacterial species and their associated toxins. A 3-year (2018–2020) survey was conducted at three different sampling sites of Dal Lake namely, Grand Palace Gath (S1), Nigeen basin (S2), and Gagribal basin (S3). Two strains of Dolichospermum sp. AE01 and AE02 (S3 and S1 site) and one strain of Microcystis sp. AE03 (S2 site) was isolated, cultured, and characterized phylogenetically by 16S ribosomal DNA sequencing. The presence of cyanotoxin genes from the isolates was evaluated by PCR of microcystins (mcyB), anatoxins (anaC), and cylindrospermopsins (pks) biosynthesis genes. Results revealed the presence of both mcyB and pks gene in Microcystis sp. AE03, and only anaC gene in Dolichospermum sp. AE02 strain. However, Dolichospermum sp. AE01 strain was not found to harbor any such genes. Our findings, for the first time, reported the coexistence of pks and mcyB in a Microcystis AE03 strain. This study has opened a new door to further characterize the unexplored cyanobacterial species, their associated cyanotoxin biosynthetic genes, and the intervention of high-end proteomic techniques to characterize the cyanotoxins.